Strategy for Diversifying Tourist Attractions to Increase the Appeal of the Tourist Village of Tomok Parsaoran Simanindo, Samosir Regency - Muhammad Khadry (Brilliant International Journal Of Management And Tourism, 2025)
This research is a descriptive qualitative study conducted in Tomok Tourism Village, Simanindo Sub-district, Samosir Regency. The study aims to identify the causes of limited diversification of tourist attractions and to design strategies for developing attractions based on local culture. The findings indicate that the dominance of traditional attractions that are not creatively packaged, the lack of community training, and the underdeveloped institutional and promotional strategies are the main challenges. The proposed development strategy adopts a Strength-Opportunity (S-O) approach, focusing on enhancing community capacity, fostering cross-sector collaboration, and preserving Batak Toba culture through innovative cultural attractions. As an implementable solution, a Business Model Canvas (BMC) was designed to support the systematic management of cultural-based attractions. The BMC model includes key partners such as local government, universities, MSMEs, and the tourism awareness group (Pokdarwis); key activities such as thematic attraction development, community training, and digital promotion; and key resources including Batak culture, trained local human resources, and the surrounding natural environment. The value propositions highlight authentic and participatory cultural experiences. Customer segments include cultural tourists, students, and digital-savvy travelers. Distribution channels focus on digital platforms, travel agents, and tourism events. The cost structure includes attraction development, training, promotion, and infrastructure. Revenue streams come from entrance fees, MSME product sales, tourism packages, and CSR support. This model is expected to enhance attraction diversification and strengthen Tomok Tourism Village’s position as a leading cultural destination in the Lake Toba area.